2011
DOI: 10.1016/j.chembiol.2011.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Specific Cell-Permeable Inhibitor of Proteasome Trypsin-like Sites Selectively Sensitizes Myeloma Cells to Bortezomib and Carfilzomib

Abstract: Summary Proteasomes degrade the majority of proteins in mammalian cells, are involved in the regulation of multiple physiological functions, and are established targets of anti-cancer drugs. The proteasome has three types of active sites. Chymotrypsin-like sites are the most important for protein breakdown and have long been considered the only suitable targets for anti-neoplastic drugs; however, our recent work demonstrated that inhibitors of caspase-like sites sensitize malignant cells to inhibitors of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(121 citation statements)
references
References 38 publications
5
107
0
5
Order By: Relevance
“…In an elegant series of experiments employing subunit‐specific reagents, Kisselev and co‐workers (Kisselev et al , 2006; Fuchs et al , 2008; Britton et al , 2009; Mirabella et al , 2011) demonstrated that: (i) inhibition of CT‐L activity alone only rescued 11–50% of degradation, adding T‐L inhibition increased this to 40–68%, while blocking all three subunits prevented protein breakdown by 73–91%; (ii) approximately half of MM cell lines tolerated 80–95% specific inhibition of CT‐L activity for 48 h with no loss of viability; and (iii) the pro‐apoptotic activity of BTZ and CFZ in MM cells (but not in normal PBMCs) was enhanced by addition of specific inhibitors of C‐L or T‐L or, most effectively, both. Consistent with the latter point, MRZ has been shown to act synergistically with BTZ in vitro and in vivo (Chauhan et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In an elegant series of experiments employing subunit‐specific reagents, Kisselev and co‐workers (Kisselev et al , 2006; Fuchs et al , 2008; Britton et al , 2009; Mirabella et al , 2011) demonstrated that: (i) inhibition of CT‐L activity alone only rescued 11–50% of degradation, adding T‐L inhibition increased this to 40–68%, while blocking all three subunits prevented protein breakdown by 73–91%; (ii) approximately half of MM cell lines tolerated 80–95% specific inhibition of CT‐L activity for 48 h with no loss of viability; and (iii) the pro‐apoptotic activity of BTZ and CFZ in MM cells (but not in normal PBMCs) was enhanced by addition of specific inhibitors of C‐L or T‐L or, most effectively, both. Consistent with the latter point, MRZ has been shown to act synergistically with BTZ in vitro and in vivo (Chauhan et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although data from our group demonstrated that combined inhibition of β5 and LMP7 was necessary and sufficient to induce apoptosis in myeloma cells in vitro (Parlati et al , 2009), several studies have postulated a role for the other active sites of the i20S in anti‐myeloma responses. Kuhn et al (2009) have shown that LMP2‐selective inhibitors can induce myeloma cell death, and multiple reports have demonstrated synergistic tumour cell killing with carfilzomib or bortezomib and either an LMP2/β1 or MECL1/β2 selective inhibitor (Britton et al , 2009; Mirabella et al , 2011). It is possible that the simultaneous inhibition of multiple i20S subunits contributes to the potent anti‐tumour activity of carfilzomib in patients with MM, including patients that are refractory to bortezomib (Siegel et al , 2012; Vij et al , 2012a), particularly given that approximately 75% of the proteasomes in isolated myeloma cells are i20S.…”
Section: Discussionmentioning
confidence: 99%
“…Substrates for LMP2 and MECL1 are poorly defined and, similar to LLVY‐AMC, do not differentiate between immunoproteasome subunit activity and the corresponding constitutive proteasome subunits (Groettrup et al , 2010). Studies utilizing inhibitors that specifically target the caspase‐like or trypsin‐like active sites suggest that inhibition of non–CT‐L active sites alone may sensitize cancer cells to CT‐L inhibition but are not sufficient to induce cytotoxicity (Britton et al , 2009; Mirabella et al , 2011). Other assessment tools are needed to fully characterize the role of c20S and i20S active sites in the anti‐cancer activity of proteasome inhibitors.…”
mentioning
confidence: 99%
“…Recently, a series of α',β'epoxyketone inhibitors that target the TL activities of the cCP and iCP was published [77] .…”
Section: Subunit-specific Proteasome Inhibitors and Their Therapeuticmentioning
confidence: 99%